2015
DOI: 10.1007/s12012-015-9338-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Interleukin-1 beta to Suppress Sympathoexcitation in Hypothalamic Paraventricular Nucleus in Dahl Salt-Sensitive Hypertensive Rats

Abstract: Findings from our laboratory indicate that expressions of some proinflammatory cytokines such as tumor necrosis factor, interleukin-6 and oxidative stress responses are increased in the hypothalamic paraventricular nucleus (PVN) and contribute to the progression of salt-sensitive hypertension. In this study, we determined whether interleukin-1 beta (IL-1β) activation within the PVN contributes to sympathoexcitation during development of salt-dependent hypertension. Eight-week-old male Dahl salt-sensitive (S) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…On the other hand, Syk, the downstream protein of Mincle, regulates NLRP3 activity via the production of reactive oxygen species . Qi et al observed increased NLRP3 expression within the PVN in salt‐sensitive hypertension rats compared with the normal rats and chronic antagonism of IL‐1β in the PVN decreased the levels of NLRP3. However, we did not found that NLRP3 expression was decreased following administration of IL‐1β inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Syk, the downstream protein of Mincle, regulates NLRP3 activity via the production of reactive oxygen species . Qi et al observed increased NLRP3 expression within the PVN in salt‐sensitive hypertension rats compared with the normal rats and chronic antagonism of IL‐1β in the PVN decreased the levels of NLRP3. However, we did not found that NLRP3 expression was decreased following administration of IL‐1β inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…112 rats were randomly divided into six groups: (a) naïve, n = 14; (b) scramble siRNA, n = 16; (c) LPS (Sigma‐Aldrich, St. Louis, MO, USA, 12.5 μg of LPS dissolved in 50 nL of saline), n = 17; (d) LPS+rSAP130 (Abnova, Taiwan, China, 25 ng in 50 nL of saline), n = 21; (e) LPS+rSAP130 + NLRP3 siRNA (Thermo Fisher, 250 pmol/50 nL), n = 22; (f) LPS+rSAP130 + gevokizumab (XOMA 052; XOMA Corporation, Emeryville, CA, USA, 50 nL of saline solution containing 10 μg of gevokizumab), n = 22. The doses of reagents were referred according to previous studies . Animals in naïve group did not receive any procedure except anesthesia until RSNA measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have detailed the pathogenesis of hypertensive disorders and reported that the molecular inflammasome platform represents a central pathogenic mechanism in initiating and promoting organ damage attributed to hypertension. Eight-week-old male Dahl salt-sensitive rats fed with a high-salt diet (8% NaCl) for six weeks were found to have higher levels of NLRP3 and IL-1β in the hypothalamic paraventricular nucleus when compared to rats fed a normal diet (0.3% NaCl) [84]. Similarly, bilateral hypothalamic paraventricular nucleus injection of an IL-1β inhibitor, gevokizumab (1 µL of 10 µg), reduced the mean arterial pressure, heart rate, and levels of plasma norepinephrine, as well as, attenuated the levels of oxidative stress (NOX-2 and NOX-4) and restored the levels of NLRP3, IL-1β, and IL-10 [84].…”
Section: Activation Of Inflammasomes In Hypertensive Disordersmentioning
confidence: 95%
“…Eight-week-old male Dahl salt-sensitive rats fed with a high-salt diet (8% NaCl) for six weeks were found to have higher levels of NLRP3 and IL-1β in the hypothalamic paraventricular nucleus when compared to rats fed a normal diet (0.3% NaCl) [84]. Similarly, bilateral hypothalamic paraventricular nucleus injection of an IL-1β inhibitor, gevokizumab (1 µL of 10 µg), reduced the mean arterial pressure, heart rate, and levels of plasma norepinephrine, as well as, attenuated the levels of oxidative stress (NOX-2 and NOX-4) and restored the levels of NLRP3, IL-1β, and IL-10 [84]. Additionally, via inhibiting NLRP3-induced inflammation and idiopathic pulmonary fibrosis, the clinically used TGF-β blocker, pirfenidone protected against thoracic aortic constriction (TAC)-induced hypertension and left ventricular hypertrophy, collectively contributing to myocardial fibrosis, via blocking NLRP3-mediated inflammation and fibrosis [85].…”
Section: Activation Of Inflammasomes In Hypertensive Disordersmentioning
confidence: 95%
“…22,23 Several elements in the hypertension-induced tissue injury are capable of acting as danger-associated molecular patterns that activate the innate immunity. In the deoxycorticosterone acetate-salt hypertension model 47 and in the Dahl SS rat, 48 the elements of the inflammasome are overexpressed. In the spontaneously hypertensive rat, the priming signals for inflammasome activation, including overexpression of Toll-like receptors 2 and 4 49 and nuclear factor kappa B activation, 50 have been demonstrated, and mRNA stimulation with overexpression of all the components of the canonical nod-like receptor pyrin 3 inflammasone are present (unpublished).…”
Section: Innate and Adaptive Immunity In The Pathogenesis Of Hypertenmentioning
confidence: 99%